THE IMPACT OF TRAFFIC AS A CAUSE OF PSYCHOLOGICAL BARRIERS AND THE DEVELOPMENT OF PHOBIAS - Siqueira Campos, Floyd (Revista Gênero e Interdisciplinaridade, 2023)
The theme proposed in this bibliographic review seeks to understand the psychological barriers caused by the impact of traffic on the lives of subjects, contextualizing the role of traffic psychology and how it can help individuals to reframe their experiences in traffic, identifying and treating phobias to restore functional behavior in the field of traffic. In order for the work to reach its objective, it was necessary to use books, articles, monographs, dissertations, among others, configuring a bibliographical research, which made it possible to understand how harmful the emotional scars and sequelae that traffic can leave in individuals and the need for awareness about the psychological damage caused by the behavior of individuals in traffic and the measures that can be taken to prevent and/or treat phobias arising from traffic.